2014
DOI: 10.1371/journal.pone.0095023
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Aberrant Astrocyte Hemichannel Activity in Juvenile Neuronal Ceroid Lipofuscinosis (JNCL)

Abstract: Juvenile Neuronal Ceroid Lipofuscinosis (JNCL) is a lysosomal storage disease caused by an autosomal recessive mutation in CLN3 that leads to vision loss, progressive cognitive and motor decline, and premature death. Morphological evidence of astrocyte activation occurs early in the disease process and coincides with regions where neuronal loss eventually ensues. However, the consequences of CLN3 mutation on astrocyte function remain relatively ill-defined. Astrocytes play a critical role in CNS homeostasis, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
71
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 47 publications
(77 citation statements)
references
References 91 publications
6
71
0
Order By: Relevance
“…PF‐06266047 also led to significant reductions in microglial activation (see Fig 4C, D). GFAP immunoreactivity was significantly enhanced in the S1BF and TH of Cln3 Δex7/8 mice as compared to WT controls, in agreement with previous observations from us and others 6, 7. Roflumilast significantly reduced GFAP immunoreactivity in both brain regions of Cln3 Δex7/8 mice (Fig 5A, B).…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…PF‐06266047 also led to significant reductions in microglial activation (see Fig 4C, D). GFAP immunoreactivity was significantly enhanced in the S1BF and TH of Cln3 Δex7/8 mice as compared to WT controls, in agreement with previous observations from us and others 6, 7. Roflumilast significantly reduced GFAP immunoreactivity in both brain regions of Cln3 Δex7/8 mice (Fig 5A, B).…”
Section: Resultssupporting
confidence: 92%
“…Additionally, Cln3 Δex7/8 astrocytes show reduced expression of the glutamate transporter GLAST and glutamine synthetase, indicating altered glutamate recycling capacity, which supports the neurotransmitter imbalance associated with JNCL 6, 9, 10, 11. We have also reported that Cln3 Δex7/8 microglia are primed toward a proinflammatory phenotype when exposed to danger signals present in the Cln3 Δex7/8 brain 8.…”
Section: Resultssupporting
confidence: 61%
See 3 more Smart Citations